Utilization of Used Cooking Oil to Make Aromatherapy Candles for PKK Women in Pasuruhan Puring Village, Kebumen - Luthfi Zamakhsyari (Journal of Society, Community and Business Development, 2024)
Used cooking oil is leftover oil from frying which is usually produced from household cooking activities. Used cooking oil is one of the waste raw materials that is growing rapidly in the household environment and has a negative impact on body health and the environment. Efforts to use used cooking oil are useful for minimizing used cooking oil waste and reducing environmental pollution. The aim of this service activity is to reduce environmental pollution due to waste from used cooking oil or used cooking oil by processing it into aromatherapy candles. The used cooking oil waste was then developed to be made into aromatherapy candles. The method used is socialization, training and direct practice to increase participants' abilities and creativity. It is hoped that from the training that has been carried out, the participants will have knowledge and insight in processing used cooking oil and at the same time can become a creative and innovative business idea.